Current sensor based on microfiber knot resonator - Lim, Kok Sing; Harun, Sulaiman Wadi; Damanhuri, Siti Sarah Ahmad; Jasim, Ali Abdulhadi; Tio, C.K.; Ahmad, Harith (Elsevier, 2011)
A compact current sensor using a microfiber knot resonator (MKR) is demonstrated. With the assistance of a copper wire that is wrapped by the microfiber knot, resonant wavelength inside the MKR can be tuned by applying electric current to the copper wire. The resonant wavelength change is based on the thermally induced optical phase shift in the MKR due to the heat produced by the flow of electric current over a short transit length. It is shown that the wavelength shift is linearly proportional to the square of the amount of current and the maximum tuning slope of 51.3 pm/A2 is achieved using a newly fabricated MKR.